Learning Arabic Pegon for Non-Javanese Santri at Pesantren - Abdul Aziz; Saliha Sebgag; Muhammad Mujtaba Mitra Zuana; Ira Suryani (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2022)
The difficulty of non-Javanese students learning Arabic and Islam using the Pegon method is a research topic that has yet to receive much attention from academics. This article aims to analyze the difficulties of non-Javanese students in the Pegon Method. Data were obtained through interviews, observation, and document analysis. The results of this study indicate that the difficulties of non-Javanese students are caused by the Javanese language used in the Pegon method. Furthermore, the Arabic or Hijaiyah letters used to write Pegon Javanese are slightly different from the original Arabic, and the scientific foundation of Arabic for students needs to be improved. Preparatory class programs, peer tutoring, and literature translation using the Pegon script into Indonesian are some strategies for anticipating student difficulties.